2008
DOI: 10.1016/j.cell.2008.07.015
|View full text |Cite
|
Sign up to set email alerts
|

A Polymeric Protein Anchors the Chromosomal Origin/ParB Complex at a Bacterial Cell Pole

Abstract: Bacterial replication origins move towards opposite ends of the cell during DNA segregation. We have identified a proline-rich polar protein, PopZ, required to anchor the separated Caulobacter crescentus chromosome origins at the cell poles, a function that is essential for maintaining chromosome organization and normal cell division. PopZ interacts directly with the ParB protein bound to specific DNA sequences near the replication origin. As the origin/ParB complex is being replicated and moved across the cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

20
471
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 299 publications
(491 citation statements)
references
References 34 publications
20
471
0
Order By: Relevance
“…39 and 40). This polar anchoring is required for effective chromosome segregation and cell division (39,40). Here, we showed that the orientation of the Caulobacter chromosome within the cell appears to be achieved by ''clocking'' the DNA molecule relative not to Cori but rather to parS.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…39 and 40). This polar anchoring is required for effective chromosome segregation and cell division (39,40). Here, we showed that the orientation of the Caulobacter chromosome within the cell appears to be achieved by ''clocking'' the DNA molecule relative not to Cori but rather to parS.…”
Section: Discussionmentioning
confidence: 85%
“…Clearly, there is a strong selective pressure for bacterial chromosomes to remain organized inside the cell, perhaps to coordinate DNA segregation with cell division. Indeed, RacA-mediated anchoring in B. subtilis prevents the formation of DNA-free forespores (41), and loss of polar parS/ParB anchoring in Caulobacter leads to defects in cell division (39,40).…”
Section: Discussionmentioning
confidence: 99%
“…The latter requirement may be due to the fact that chromosome II has many properties of a large plasmid and its Par proteins are more closely related to plasmid-encoded ones than to those encoded on chromosomes (22). In C. crescentus, the par system may be essential only indirectly, as it is used for proper localization of the cell division machinery through at least two other proteins, PopZ (6,13) and MipZ (53). PopZ captures the parB/ori complex and subsequently anchors it at opposite cell poles (6,13).…”
mentioning
confidence: 99%
“…In C. crescentus, the par system may be essential only indirectly, as it is used for proper localization of the cell division machinery through at least two other proteins, PopZ (6,13) and MipZ (53). PopZ captures the parB/ori complex and subsequently anchors it at opposite cell poles (6,13). This results in the FtsZ polymerization inhibitor MipZ, which also forms a complex with ParB, to localize to the poles.…”
mentioning
confidence: 99%
“…This process repeats until one ParB-parS complex moves across the cell where it becomes anchored to the cell pole by the polarly localized protein PopZ. (Bowman et al, 2008;Ebersbach et al, 2008).…”
Section: Introductionmentioning
confidence: 99%